A case of carbamazepine-induced toxic epidermal necrolysis in an Afghan woman - Muhammad Ijaz; Iftikhar Ali; Khatira Wahid; Aziz Ullah Khan (Archives of Global Professionals, 2016)
We present a case of a 55-year-old diabetic woman who presented to the clinic with an erythematous, scaly, itchy rash and generalized abdominal pain with vomiting. Owing to the symptoms of peripheral neuropathy, she had been prescribed carbamazepine 100 mg twice daily. Initially, the patient presented with the rash on her face along with sticky eyelashes, which later spread to chest, abdomen, and thighs. Blood cultures and wound swabs were taken, carbamazepine was stopped, a working diagnosis of toxic epidermal necrolysis (TEN) with prerenal acute kidney injury was made. Her renal functions were deranged with a serum urea of 170 mg/dL, serum creatinine 3.3 mg/dL, lactic acid 43 mg and estimated glomerular filtration rate (eGFR)15.3 ml/min/1.73 m2. There was no biochemical improvement observed, postdialysis. She developed left leg arterial ischemia with numbness, bluish discoloration of the skin, and hypotension. Ultimately, the patient went into multi-organ failure and unfortunately passed away. Serious and, sometimes, fatal dermatological reactions have been reported during the treatment with carbamazepine. Although carbamazepine-induced TEN is not a rare presentation, other similar drugs with a safer side effect profile could be used instead as in the case of our patient.